Added Taxes in the ASEAN-Pacific Region (Malaysian Management Journal, 2004)
The Value Added Tax (or Goods and Services Tax) is the most popular form of general indirect tax in the world today. Of the ASEAN countries, only Myanmar, Brunei, Laos and Malaysia do not currently have a VAT, though the latter will introduce one in 2007. In the neighbouring Pacific region, both Australia and New Zealand have GSTs in place. This paper surveys the main features of the VATs/GSTs currently found in the ASEAN-Pacific region. In terms of structure, they range from the very simple and comprehensive taxes found in Singapore and New Zealand, to the highly complex VAT of Vietnam, which has two main rates and a multitude of exempt commodities. The administrative arrangements used to assess and collect the tax differ in detail but include a number of common features, such as exemptions for small businesses, simple invoice requirements for low-value transactions, and assessment on an invoice basis for large business, with a cash basis available to small business. The information and comparisons presented here are highly relevant for countries contemplating or planning the introduction of a VAT, such as Malaysia, and for countries in the region considering modifications to the tax. In general, the more comprehensive the tax, the simpler the administrative procedures required, the less the explanatory material that needs to be produced to educate the business community, and the greater the revenue-raising power of the tax.